Microbiota and hepatic diseases - T. E. Polunina (Лечащий Врач)
The data on the existing knowledge in the field of intestinal microbiota influence on human diseases were presented, in particular, non-alcoholic fat liver disease, alcoholic liver disease, inflammatory intestinal diseases and infectious gastrointestinal diseases. Possibility of intestinal microbiota correction in wide-spread liver diseases was evaluated, considering the recent and most significant evidence related to antibiotics, probiotics, prebiotics and metabiotics.